Question
upstudy study bank question image url

QUESTION 3 The equation of a hyperbola is given by \( f(x)=\frac{3}{x-7}-4 \). Write down the equation of the new function that is formed when \( f \) is transformed as follows: \( 3.1 \quad \) Shift two units to the left \( 3.2 \quad \) Shift 3 units up \( 3.3 \quad \) Shift 1 unit right and 2 units down \( 3.4 \quad \) The equation of the new hyperbola has new asymptotes at \( x=-4 \) and \( y=-1 \)

Ask by Campbell Weber. in South Africa
Dec 29,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

After all transformations, the new hyperbola equation is: \[ f(x) = \frac{3}{x + 4} - 1 \] with asymptotes at \( x = -4 \) and \( y = -1 \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

The Deep Dive

To transform the function \( f(x)=\frac{3}{x-7}-4 \) according to the specified shifts, we can break it down step by step. \( 3.1 \quad \) Shifting two units to the left means we replace \( x \) with \( x + 2 \): \[ f_1(x) = \frac{3}{(x + 2) - 7} - 4 = \frac{3}{x - 5} - 4. \] \( 3.2 \quad \) Shifting three units up involves adding 3 to the entire function: \[ f_2(x) = \frac{3}{x - 5} - 4 + 3 = \frac{3}{x - 5} - 1. \] \( 3.3 \quad \) Shifting 1 unit right and 2 units down requires us to replace \( x \) with \( x - 1 \) and subtracting 2: \[ f_3(x) = \frac{3}{(x - 1) - 5} - 1 - 2 = \frac{3}{x - 6} - 3. \] \( 3.4 \quad \) To adjust the asymptotes to \( x = -4 \) and \( y = -1 \), we rewrite the hyperbola: The standard form is \( f(x) = \frac{a}{x-h} + k \), where \( h \) is the x-coordinate of the vertical asymptote and \( k \) is the y-coordinate of the horizontal asymptote. Thus, the equation becomes: \[ f(x) = \frac{3}{x + 4} - 1. \] So the final answers are as follows: - \( 3.1: \quad f_1(x) = \frac{3}{x - 5} - 4 \) - \( 3.2: \quad f_2(x) = \frac{3}{x - 5} - 1 \) - \( 3.3: \quad f_3(x) = \frac{3}{x - 6} - 3 \) - \( 3.4: \quad f_4(x) = \frac{3}{x + 4} - 1 \)

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy